Penerapan “SI GADIR” Untuk Meningkatkan Self Esteem Siswa Kelas X SMK Negeri 1 Trenggalek - Fitriani, Vivi Yuniar; Isnari, Insari; Isnari, Isnari (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2020)
The research objective was to see the effectiveness of "si gadir" to increase the self-esteem of vocational students. The research method is an experiment using a pretest-posttest group design involving 10 students who have low self-esteem as group members. The results showed that there was an increase in students' self-esteem before being given "si gadir" of 1.028 (SD 6.12) to 1.308 (SD 5.90; t (10) = 8.89, p <0.01). This research was conducted that si gadir (simulasi harga diri) can be applied to increase students' self-esteem.